Sustained-release genistein from nanostructured lipid carrier suppresses human lens epithelial cell growth - Liu, Jin-Lu (Int J Ophthalmol, 2016)
AIM: To design and investigate the efficacy of a modified nanostructured lipid carrier loaded with genistein (Gen-NLC) to inhibit human lens epithelial cells (HLECs) proliferation. METHODS: Gen-NLC was made by melt emulsification method. The morphology, particle size (PS), zeta potentials (ZP), encapsulation efficiency (EE) and in vitro release were characterized. The inhibition effect of nanostructured lipid carrier (NLC), genistein (Gen) and Gen-NLC on HLECs proliferation was evaluated by cell counting kit-8 (CCK-8) assay, gene and protein expression of the proliferation marker Ki67 were evaluated with real-time quantitative polymerase chain reaction (RT-qPCR) and immunofluorescence analyses. RESULTS: The mean PS of Gen-NLC was 80.12±1.55 nm with a mean polydispersity index of 0.11±0.02. The mean ZP was -7.14±0.38 mV and the EE of Gen in the nanoparticles was 92.3%±0.73%. Transmission electron microscopy showed that Gen-NLC displayed spherical-shaped particles covered by an outer-layer structure. In vitro release experiments demonstrated a prolonged drug release for 72h. The CCK-8 assay results showed the NLC had no inhibitory effect on HLECs and Gen-NLC displayed a much more prominent inhibitory effect on cellular growth compared to Gen of the same concentration. The mRNA and protein expression of Ki67 in LECs decreased significantly in Gen-NLC group. CONCLUSION: Sustained drug release by Gen-NLCs may impede HLEC growth.